2007
DOI: 10.1159/000103257
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Lower Serum Albumin and Vitamin D Levels Are Associated with Decreased Objective Physical Performance among Japanese Community-Dwelling Elderly

Abstract: Background: Previous studies have shown that serum albumin or vitamin D is associated with physical performance. We hypothesized that older adults with concomitant lower serum albumin and vitamin D (25-hydroxyvitamin D, 25OHD) levels are associated with decreased physical performance compared to those with 1 or none of the 2 risk factors. Objective: To investigate the association of combined serum albumin and 25OHD levels with physical performance (muscle strength and balance capability) in community-dwelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 38 publications
(42 reference statements)
5
39
1
Order By: Relevance
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women. However, this result was less reliable than previous studies because no adjustments for confounders were made.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(10,(16)(17)(18)(19)(20)(21)(22) It has been shown that ambulation time over an 8-ft walkway correlated with higher serum 25(OH)D concentrations. (10,18) Gerdhem and colleagues (19) also have reported a positive significant linear correlation with usual walking speed in a cohort of 986 elderly women. However, this result was less reliable than previous studies because no adjustments for confounders were made.…”
Section: Discussionmentioning
confidence: 99%
“…However, this result was less reliable than previous studies because no adjustments for confounders were made. Additionally, Kwon and colleagues (18) showed that men with concomitantly low serum albumin and 25(OH)D concentrations had a low timed up and go score, even after adjusting for age and BMI. Finally, Suzuki and colleagues (16) recently highlighted a positive significant linear association with walking speed at a usual pace for either men or women in a larger cohort of 2957 Japanese subjects aged 65 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations